Unexpected Lung and Brain Metastases 9 Years After Thyroid Lobectomy for Follicular Adenoma: A Case Report - Lee, Yoo Jin; Kim, Dong Wook; Shin, Gi Won; Heo, Young Jin; Park, Jin Young; Baek, Jin Wook; Choo, Hye Jung; Cho, Young Jun; Park, Ha Kyoung; Ha, Tae Kwun; Kim, Do Hun; Jung, Soo Jin; et al. (Frontiers in Endocrinology, 2019)
Background: Benign thyroid follicular tumors without histological evidence of carcinoma can metastasize. However, the pathogenesis of metastasis remains unclear. Here, the new proposed terminology, “non-invasive follicular thyroid neoplasm with papillary-like nuclear features” should be considered. We present a case of an encapsulated type of follicular variant of papillary thyroid carcinoma (FVPTC) that exhibited distant lung and brain metastases and was initially diagnosed as follicular adenoma. Case Report: In December 2006, a 64-year-old woman underwent ultrasonography-guided fine-needle aspiration of the right thyroid nodule at our hospital because of a palpable right neck mass. Right lobectomy was performed, and a follicular adenoma was diagnosed. In October 2015, she visited our hospital owing to dry cough and mild dyspnea and underwent computed tomography-guided transthoracic core needle biopsy for the lung nodule owing to probably multiple lung metastasis on chest X-ray and computed tomography. Based on retrospective analysis of the primary thyroid tumor and lung nodule specimen, an encapsulated follicular variant of papillary thyroid carcinoma with lung metastasis was confirmed. Conclusion: We report a case of an encapsulated follicular variant of papillary thyroid carcinoma with unexpected metastasis to the lung 9 years after thyroid surgery in a patient who was initially diagnosed as follicular adenoma. A careful close follow-up with re-examination of the histopathology specimen may be needed in patients who were diagnosed with benign thyroid follicular tumors.